Consciousness and politics from analysis to meditation in the late work of Eric Voegelin - Cooper, Barry 1943- (St. Augustine's Press, 2018)
"Consciousness and Politics begins with an analysis of the problem of the historicity of truth as it was formulated shortly before Voegelin abandoned his eight-volume History of Political Ideas. The analysis then follows a more or less chronological path, discussing the arguments developed in The New Science of Politics, Voegelin's most famous book, the differentiation of consciousness and the problems of myth and nature as presented in the early volumes of Order and History. Starting in the 1960s, Voegelin began a lengthy argument in several volumes that resumed his concern with the philosophy of consciousness, which he had outlined in his early writings, and its connection to what we conventionally call philosophy of history. Voegelin's late and often difficult essays, lectures, and the final volume of Order and History, many scholars have noticed, emphasize the meditative origins of his political science and, more broadly, of philosophy. The concluding chapters analyze this subject-matter and a perennial question that so many of Voegelin's readers have raised: what is the relation of his political science or philosophy to Christianity?"...